2016
DOI: 10.1039/c5cc09412g
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal to single crystal [2+2] photoreactions in chloride and sulphate salts of 4-amino-cinnamic acid via solid-solution formation: a structural and kinetic study

Abstract: A set of molecular salts with general formula [1H]nA·xH2O (1 = 4-amino-cinnamic acid, A(n-) = NO3(-), BF4(-), PF6(-), SO4(2-), x = 0, 1) was prepared and structurally characterized. [1H]Cl and [1H]2SO4·H2O(II) were found to undergo an SCSC stepwise [2+2] photodimerization, which was followed by X-ray diffraction; a kinetic analysis was performed on single crystals of both salts. In the case of [1H]Cl the photoreaction was also studied on polycrystalline materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
2
26
1
Order By: Relevance
“…With this in mind we have prepared and investigated the [2 + 2] photoreactivity in a series of molecular salts with the general formula [1H] n AÁxH 2 O (1 = 4-amino-cinnamic acid, A nÀ = NO 3 À , BF 4 À , PF 6 À , SO 4 2 À , x = 0, 1). Amongst all, only the chloride and sulfate salts were found to undergo SCSC [2 + 2] photodimerization to generate the corresponding -dimers containing crystals (d'Agostino et al, 2016). Moreover, the conversions were followed stepwise by single-crystal X-ray diffraction: in both cases, upon irradiation, the presence in the crystals of the cyclobutane ring was detected, and its percentage increased up to complete conversion, as shown in Fig.…”
Section: From Single-crystal-to-single-crystal Transformations To Solmentioning
confidence: 90%
“…With this in mind we have prepared and investigated the [2 + 2] photoreactivity in a series of molecular salts with the general formula [1H] n AÁxH 2 O (1 = 4-amino-cinnamic acid, A nÀ = NO 3 À , BF 4 À , PF 6 À , SO 4 2 À , x = 0, 1). Amongst all, only the chloride and sulfate salts were found to undergo SCSC [2 + 2] photodimerization to generate the corresponding -dimers containing crystals (d'Agostino et al, 2016). Moreover, the conversions were followed stepwise by single-crystal X-ray diffraction: in both cases, upon irradiation, the presence in the crystals of the cyclobutane ring was detected, and its percentage increased up to complete conversion, as shown in Fig.…”
Section: From Single-crystal-to-single-crystal Transformations To Solmentioning
confidence: 90%
“…Among all crystalline-state photopolymerization systems, photoinitiated [2 + 2] and [4 + 4] , cycloaddition reactions were mostly investigated in diene, diyne, heterocyclic derivatives, metal–organic framework, and phenanthrene-containing systems. The criteria for crystalline-state [2 + 2] cycloaddition was reported by Schmidt and co-workers. , They proposed that the center-to-center distance d between the nearest-neighbor double bonds is of the order of 4 Å through topochemical rules, and the experimental observed limit is 3.5 Å < d < 4.2 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we reveal the hydrogen-bonding capacity of organoboronic acids to direct chemical reactivity in the organic solid state (Scheme a). Specifically, we demonstrate 4-methoxy­phenyl­boronic acid ( 4-MeO-ba ) in the cocrystal ( 4-MeO-ba )·( bpe ) (where bpe = trans -1,2-bis­(4-pyridyl)­ethylene) to act as a bifunctional hydrogen-bond-donor template by assembling bpe by way of (B)­O–H···N hydrogen bonds in a discrete four-component supramolecular assembly to undergo an intermolecular [2 + 2] photodimerization.…”
mentioning
confidence: 97%
“…Specifically, studies of cocrystals and related hydrates of boronic acids with bipyridines showed the components to assemble by way of (B)­O–H···N hydrogen bonds wherein the acids enforced the pyridines to stack into face-to-face geometries. The observations prompted us to explore the use of organoboronic acids to direct the [2 + 2] photodimerization in the solid state. In the design, a boronic acid, in a syn–syn conformation (Scheme b), would support the formation of discrete four-component hydrogen-bonded molecular assemblies wherein face-to-face stacking of a pyridyl-functionalized alkene would conform to the geometry of Schmidt to undergo the photodimerization …”
mentioning
confidence: 99%